PERAN TENAGA KESEHATAN DAN MOTIVASI TERHADAP EFEKTIVITAS PELAYANAN GIZI LEBIH - Noorlinda; Sartika (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2021)
Childhood obesity is seen to look healthy and have a healthy and intelligent child is the desire of every parent. To make it happen of course parents should always pay attention to the growth and development of nutrition. Although the process of developing a child develops naturally, the process is highly dependent on adults or parents. The purpose of this study to determine the direct and indirect influence and magnitude between health the role of health workers and motivation of under-five children to the effectiveness of health services in patients with more nutrition. This research type is quantitative with cross sectional design. Number of population and sample of research are 50 mother of balita. This research was conducted at UPT Puskesmas Gebang Cirebon Regency Year 2017. The result of hypothesis test resulted the research finding that the effectiveness of health service in nutrition patient is health manpower (28.14%), and Mother Motivation (39.81%). The direct influence of health service effectiveness on nutrition patient is 25.7% and indirect influence is 0.58% and total direct and indirect influence 26.3%. Health facilities are factors that affect the effectiveness of health services in patients with more nutrition. Research suggestions for health workers at UPT Puskesmas Gebang Cirebon District, especially midwives are expected to further improve the Puskesmas service and provide information on nutritional balance, so as to reduce morbidity and mortality of infants and toddlers.